Pengaruh Kualitas Pelayanan Dan Kepuasan KonsumenTerhadap Loyalitas Pelanggan Pada Toko Alat TulisPuspita Di Pabelan - Putri, Nuri Zahidah Eka, Muzakar Isa, SE., M.Si (2016)
This research aimed at analyzing the influence the service quality and consumer's satisfaction on the customer's loyalty simultaneously in the customers of Toko Alat Tulis Puspita (Puspita Stationery Store) in Pabelan. Besides, this research also tried to analyze two independent variables in explaining the customer's loyalty. It was hoped that this research can broaden the knowledge about the customer's loyalty and becomes the reference of researches in future. Hypothesis of this research is : it was presumed that there is an influence of the service quality and consumer's atisfaction on the customer's loyalty simultaneously. The population in this research is respondents who had once conducted purchase in Toko Alat Tulis Puspita in Pabelan. The technique of sampling which was used is convenience sampling by taking samples of 100 respondents. This research used linear regression (t test, F test, and R2 test). The score of R square (R2) obtained was 0.358. It explained that the variation of change in the variable of customer's loyalty can be explained by the variable of service quality and consumer's satisfaction as much as 35.8%. meanwhile, the rest was explained by other variables outside the model.